Distribution of arabinogalactan protein (AGP) epitopes on the anther derived embryoid cultures of Brassica napus - Namasivayam, Parameswari; Skepper, Jeremy Neil; Hanke, David E. (Universiti Putra Malaysia Press, 2010)
The anther-derived embryoid cultures of Brassica napus is stably embryogenic and has an extracellular matrix (ECM) layer covering the surface of the developing embryoids. In this study, the distribution of arabinogalactan protein (AGP) epitopes in the ECM layer and the embryogenic tissue of winter oilseed rape were investigated by immuno-labelling with anti-AGP monoclonal antibodies (mAb JIM4, JIM8, and JIM 13). There was no labelling by the JIM4 and JIM8 mAbs in the ECM layer, unlike what was reported in other plant species. JIM 13 epitope is developmentally regulated because it was only present in the ECM layer of the mature embryogenic tissue. These observations indicate a possible variability in the AGP epitopes present in the ECM layer among the different plant species. JIM8 and JIM 13 epitopes were found in some epidermal cells of embryogenic tissue, but not in the non-embryogenic tissue, implying that AGPs might have a specific role in embryogenic competency or determining the cell fate of the B. napus embryogenic cells